Pengaruh Tingkat Partisipasi Angkatan Kerja (TPAK) dan Indeks Pembangunan Manusia (IPM) terhadap Pertumbuhan Ekonomi di 13 Kabupaten/Kota di Kalimantan Selatan - Margono, Amirul Wahid; Nuryadin, Muhamad Rusmin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study aims to analyze the effect of Labor Force Participation Rate (LFPR) and Human Development Index (HDI) on Economic Growth in 13 Districts/Cities of South Kalimantan. Data obtained from the secondary data which are cross section of 13 Districts/Cities and time series of 2007-2019. The method use panel data regression analysis with Fixed Effect Model via EViews 13 software program. Based on result of analysis, simultaneously Labor Force Participation Rate and Human Development Index are significant on Economic Growth in 13 Districts/Cities of South Kalimantan. Partially LFPR is significant and positive while HDI is significant and negative.